(untitled) (Indian Journal of Child Health, 2021)
Context: Vesicoureteric reflux (VUR) has been implicated in renal injury before birth as well as in postnatal occurrence of urinary tract infection (UTI) and further renal damage. About 30–49% of children with primary VUR may develop renal scarring called reflux nephropathy. About 5–10% of children with reflux nephropathy may progress to chronic kidney disease in late childhood. Objectives: The objectives of the study were to study the clinical profile of children with primary VUR and to assess the relationship with grades of primary VUR and renal parenchymal scarring. Materials and Methods: Fifty children of age 1 month–5 years, diagnosed to have Primary VUR, were included in this prospective observational study. Detailed history was taken; examination was carried out as per the study protocol. Investigations included urine analysis, renal function tests, urine culture, renal ultrasonography, micturating cystourethrogram, and 99mTc dimercaptosuccinic acid (DMSA) scintigraphy. For those who had UTI, DMSA was carried out after a minimum period of 6 months after UTI episode. Results: Among the 50 children, 21 (42%) were male and 29 (58%) were female with male-to-female ratio of 0.72:1. Mean age at diagnosis was 9 months, ranging from 1 to 40 months. The number of children presented with UTI was 43 (86%), and 7 children (14%) were asymptomatic and were evaluated in view of abnormality in prenatal ultrasound scan. Unilateral VUR was found in 21 patients (42%), and 29 patients (58%) had bilateral VUR. Of all 79 refluxing units (21 unilateral plus 58 bilateral), 4% had VUR of Grade I severity, 30% of Grade II, 34% of Grade III, 28% of Grade IV, and 4% of Grade V severity. Renal parenchymal scarring on DMSA scan was detected in 42 (54%) of 79 refluxing units including 33% of Grade II, 55% of Grade III, 71% of Grade IV, and 100% of Grade V refluxing units. Prevalence of scarring in complicated, recurrent, and simple UTI was 100%, 93%, and 22%, respectively. Conclusion: Risk of renal scarring increased progressively with increasing severity of primary VUR. Complicated and recurrent UTI were found to be statistically significant risk factors for renal scarring. Renal scarring was also seen in absence of UTI in a small percentage of children with primary VUR.